Core Stability Exercise Intervention for Managing Pain and Flexibility in Nurses with Non-Specific Low Back Pain - Nazli Alamri; Rahmania Ambarika; Novita Anna Anggraen (Health and Technology Journal (HTechJ), 2025)
Low Back Pain (LBP) affected 619 million people globally in 2020, and the number is projected to increase to 843 million by 2050. Among nurses, the prevalence of LBP reaches 72%, with significant risk factors including long working hours, poor posture, and heavy workloads. This condition negatively impacts nurses' well-being, productivity, and the quality of healthcare services. Physiotherapy interventions, particularly core stability exercises, have been proposed as a practical approach to reduce pain and improve functional mobility. This study aimed to examine the effect of core stability exercise on pain intensity and flexibility in nurses with non-specific LBP. A proper experimental study with a pre–post test control group design was conducted. A total of 47 nurses who met the inclusion criteria were recruited using simple random sampling. Pain intensity and flexibility were measured before and after the intervention. Data were analyzed using the paired sample t-test. Core stability exercise significantly reduced pain intensity (p = 0.000, <0.05) and significantly improved flexibility (p = 0.000, <0.05). These findings indicate that the intervention positively impacted musculoskeletal health among nurses with non-specific LBP. Core stability exercise is an effective intervention for reducing pain and enhancing flexibility in nurses with non-specific LBP. Activating core muscles through exercise promotes vasodilation, improves blood circulation, and increases oxygen and nutrient delivery to myofascial tissue, producing analgesic effects. In addition, coordinated muscle contractions enhance lumbar stability, reduce intervertebral disc pressure, and minimize muscle tension, improving functional flexibility.